A modified integer programming model for cleaning service scheduling / Zuraida Alwadood, Hamidah Ayub and Muhamad Ariff Izzuddin Razali - Alwadood, Zuraida; Ayub, Hamidah; Razali, Muhamad Ariff Izzuddin (Research Management Institute (RMI), 2010)
This paper analyzes the problem faced by a cleaning service company, which records and pays out a large amount ofovertime each month. With only one shift per day, the labor force is required to work overtime in order to satisfy the daily work demand The objective ofthis paper is to determine the optimum schedule to satisfy the labor requirements at a minimum cost. Tiberwala et al. s (1972) single-shift integer programming model for scheduling workers with two consecutive days offper week has been used as the starting point for this research. This paper modifies the model to incorporate two and three shift schedules with one day offper week. Three alternative workforce schedules are then comparedandevaluated. Thefirst alternative maintains the traditional one-shift schedule, currently being practiced by the company. The second and third alternatives switch to a two-shift schedule and three-shift schedule, respectively, with overlapping working hours linking the shifts. In comparison to the existing one-shift schedule, the three-shift schedule is expected toproduce savings 0/21.4 per cent equivalent to RM23,592 annually.